2020
DOI: 10.3390/pharmacy8020051
|View full text |Cite
|
Sign up to set email alerts
|

T.E.A.M.S.Work: Leveraging Technicians to Enhance ABM Med Sync in Community Pharmacies

Abstract: The expansion of pharmacy technicians’ roles in community pharmacies allows pharmacists the opportunity to focus on providing clinical services to patients. This study explores the tasks pharmacy technicians’ perform to support Med Sync programs in community pharmacies. Pharmacy staff members at North Carolina pharmacies with more than fifty percent of their prescription volume being dispensed as part of a Med Sync program were recruited to participate in semi-structured interviews. Inductive coding and summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Med sync programs have the potential to greatly improve medication adherence, and their success will be aided by further standardization of operational processes [ 4 ].Among those processes include a redefinition of technician roles and the use of appointment-based models (ABM) to facilitate patient interaction and prospective drug utilization review. The first of the two articles on med sync ABM employedqualitativeresearch to describe technicians’ job descriptions for this type of service [ 5 ]. The tasks in which techniciansmight assume greatest responsibility include identifying patients for marketing and enrollment, reviewing patients’ medication lists, choosing alignment dates based on patient preference, contacting patients in preparation for dispensing, and engaging in pickup or delivery of medications.…”
mentioning
confidence: 99%
“…Med sync programs have the potential to greatly improve medication adherence, and their success will be aided by further standardization of operational processes [ 4 ].Among those processes include a redefinition of technician roles and the use of appointment-based models (ABM) to facilitate patient interaction and prospective drug utilization review. The first of the two articles on med sync ABM employedqualitativeresearch to describe technicians’ job descriptions for this type of service [ 5 ]. The tasks in which techniciansmight assume greatest responsibility include identifying patients for marketing and enrollment, reviewing patients’ medication lists, choosing alignment dates based on patient preference, contacting patients in preparation for dispensing, and engaging in pickup or delivery of medications.…”
mentioning
confidence: 99%
“…In addition to diffusions of innovations theory, implementation science can also guide successful strategies for expansion and implementation of patient care services in community pharmacy settings. 38,39 There are some studies in community pharmacies that have demonstrated success with integrating EHR access, [39][40][41] expanding technician roles, [42][43][44][45][46] and collaborating with primary care providers for patient care services. [47][48][49][50] Using diffusion of innovation theory and implementation science research can further add to the literature for expansion of patient care services in community pharmacies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, pharmacy technicians have been identified as key players in supporting Med Sync programs. 47 This suggests that a team-based approach is an effective strategy for adopting Med Sync. Furthermore, whether or not Med Sync adoption would increase the pharmacists' workload has been in question.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, participants believed having whole-team involvement helped them overcome time constraints which are often cited as a challenge when implementing clinical services in community pharmacies. 47 , 48 …”
Section: Discussionmentioning
confidence: 99%